The acting of nurse front relation to pregnant women living with HIV/Aids (Research, Society and Development, 2020)
Objective: to know the acting of nurses front pregnant women living with HIV/AIDS. Method: qualitative study, developed through semi-structured interview, with nurses from Family Health Strategies. The data were submitted to thematic content analysis. Results: the idea persists that prenatal care for pregnant women living with HIV/AIDS differs from side dish other women who do not have the disease. Nurses consider it necessary to refer this clientele to specialized services. They do not feel prepared/trained to attend these pregnant women, as they understand that they need special care and additional guidance, mainly related to exams and drug treatment. Conclusion: immediate needs relative to the theme of the study were identified, such as the need for permanent professional education, academic training for infectious diseases, flowchart in atenction prenatal care that helps in the identification and referral of pregnant women, in addition to research from the perspective of pregnant women living with HIV/AIDS.